2015
DOI: 10.1111/idj.12177
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of caries and malocclusion in an indigenous population in Chiapas, Mexico

Abstract: Less than 1% of the population had any exposure to orthodontics, demonstrating the lack of access to care. Likewise, only 1% of the population was found to have no caries experience, exhibiting a large unmet treatment need. The median DMFS score of 8 was also high in comparison with the median DMFS in the USA of 6. Our data suggest a correlation between the lack of access to care and high prevalence of caries and malocclusion in Mexican Mayans who inhabit Chiapas, Mexico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
0
12
3
2
Order By: Relevance
“…This finding is consistent with the findings of Gabris K, et al [18]; ; Buczkowska-Radlinska J, et al [17]; and Baskaradoss KL, et al [16] that demonstrated a positive association between caries prevalence and malocclusion. However, it differs with some other studies by Asahi K, et al [45]; and Aamodt K, et al [46], who did not report statistically significant association between caries and malocclusion.…”
Section: Discussioncontrasting
confidence: 88%
“…This finding is consistent with the findings of Gabris K, et al [18]; ; Buczkowska-Radlinska J, et al [17]; and Baskaradoss KL, et al [16] that demonstrated a positive association between caries prevalence and malocclusion. However, it differs with some other studies by Asahi K, et al [45]; and Aamodt K, et al [46], who did not report statistically significant association between caries and malocclusion.…”
Section: Discussioncontrasting
confidence: 88%
“…While there are standard clinical approaches for measuring dental caries and malocclusion, it is not known if the degree of malocclusion and dental caries, as determined by dental professional measures, has any relation with the perceived impact on the child. Several studies can be found regarding the prevalence of caries and malocclusion in specific areas in Latin America [7]. However, there is a paucity of studies comparing rural and urban regions within any given country.…”
Section: Introductionmentioning
confidence: 99%
“…Diferentes autores han encontrado un patrón similar en diversas poblaciones, así: Kirzioglu et al [25] encontraron que un 73,6% de la población turca evaluada presentaba una relación molar de clase i, lo que indica que este grupo fue más prevalente; sin embargo, en su estudio Emine, también en población turca, encontró mayor prevalencia de clase ii que de clase i [23]. En México, en población aborigen, se encontró mayor porcentaje de maloclusión clase ii (46,33%), seguido de la clase iii (38,98%) y, por último, la clase i (13,56%) [26]. En población albanesa, también se encontró mayor prevalencia de clase i (40%) seguida de la clase ii, (29,8%) y la maloclusión menos presente fue la clase iii [27].…”
Section: Discussionunclassified